Conformational Dynamics Allows Sampling of an "Active-like" State by Oncogenic K-Ras-GDP. Issue 17 (15th September 2022) - Grudzien, Patrick; Jang, Hyunbum; Leschinsky, Nicholas; Nussinov, Ruth; Gaponenko, Vadim
Graphical abstract: Highlights: K-Ras-GDP can sample the "active-like" conformation found in the GTP-bound state. Oncogenic mutations affect sampling of the "active-like" conformation by K-Ras-GDP. NMR chemical shifts identify conformational diversity in proteins. Abstract: Mutations in K-Ras GTPase replacing Gly12 with either Asp or Val are common in cancer. These mutations decelerate intrinsic and catalyzed GTP hydrolysis, leading to accumulation of K-Ras-GTP in cells. Signaling cascades initiated by K-Ras-GTP promote cell proliferation, survival, and invasion. Despite functional differences between the most frequent G12D mutation and the most aggressive and chemotherapy resistant G12V mutation, their long-suspected distinct structural features remain elusive. Using NMR, X-ray structures, and computational methods, we found that oncogenic mutants of K-Ras4B, the predominant splice variant of K-Ras, exhibit distinct conformational dynamics when GDP-bound, visiting the "active-like" conformational state similar to the one observed in GTP-bound K-Ras. This behavior distinguishes G12V from wild type and G12D K-Ras4B-GDP. The likely reason is interactions between the aliphatic sidechain of V12 and the Switch II region of K-Ras4B G12V -GDP, which are distinct in K-Ras4B G12D -GDP. In the X-ray structures, crystal contacts reduce the dynamics of the sidechain at position 12 by stabilizing the Switch I region of the protein. This explains why structural differences between G12V and G12D K-Ras have yet not been reported. Together, our results suggest a previously unknown mechanism of K-Ras activation. This mechanism relies on conformational dynamics caused by specific oncogenic mutations in the GDP-bound state. Our findings also imply that the therapeutic strategies decreasing the level of K-Ras-GTP by interfering with nucleotide exchange or by expediting GTP hydrolysis may work differently in different oncogenic mutants.